Synthesis and Electrochemical Investigations of a Binuclear [FeFe]‐Hydrogenase Mimic - Benedikt Callies; Kai‐Thorben Kuessner; Sven T. Stripp; Stephan Kupfer; Phil Köhler; Helmar Görls; Inke Siewert; Wolfgang Weigand (ChemElectroChem)
Herein, a [FeFe]‐hydrogenase mimic with the benzene‐1,2‐dithiolato ligand bearing two amino groups in 4‐ and 5‐position of the ligand is reported. The ligand synthesis is straight forward and accomplished in two steps. Detailed studies show that the implementation of the functional groups in the [FeFe]‐hydrogenase mimic has marginal impact on the structural, thermodynamic properties, and catalytic performance in the electrochemical proton reduction reaction. However, the modification opens the way for a wide variety of functionalization in the ligand backbone, e.g., for applications in photo/electrocatalysis. Electrochemical investigations reveal that initial two electron reductions are followed by protonation by acetic acid forming an asymmetric diironhydride species. Further reduction of the hydride species and protonation leads to H2 formation. Utilizing foot of the wave analysis, a reaction rate of 2 × 108 s−1 m−1 for the H2 evolution step consisting of the reaction of the metal hydride species and the external acid has been determined. However, catalysis is limited by the formation of the hydride at a rate constant of about 4 × 104 s−1 m−1.